ATRIBUT YANG MENJADI PERTIMBANGAN NASABAH DALAM MEMILIH BANK (Studi Kasus PT Bank Rakyat Indonesia Cabang Jambi) - Azizah Azizah (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
This study uses primary data and secondary data and the number taken in a representative sample using purposive random sampling method. Analysis tool to analyze this research uses chochran test. From the results of discussion by using the test results obtained chochran of Testing Decision I: Reject Ho because the Q count (46.4)> Q tab (16.92). So there is no common opinion of respondents about the attributes. Thus, the need to be tested II by removing attributes that have the smallest proportion of YES answers, is an attribute "bank management". Testing decision II: Reject Ho because the Q count (19.57)> Q table (15.51). Not enough evidence to suggest that the same possible answers YES for each attribute. Thus, III Tests need to be done by issuing an attribute with the smallest proportion of YES answers. Decision III testing is to accept Ho for calculating Q (12.69) <Q table (14.07). That is, there is evidence to suggest that the eight attributes have the same possible answers YES for each attribute. In other words, the 8th of attributes that were analyzed can be considered valid as attributes of a bank.Based on the contribution of the attributes that customers consider in choosing a bank to save money can be sorted by score, the types of services provided by a score of 100, the trust the public with a score of 100, the position / location of the bank with a score of 98, the bureaucracy with a score of 98. gifts or souvenirs by a score of 98, the number and spread of branches with a score of 97 interest rate by a score of 96, the facilities available with a score of 94, the capital with a score of 87, the bank management with a score of 80.